Characterization of Haptoglobin Isotype in Milk of Mastitis-Affected Cows - Upadhyaya, Indu (Vet Sci, 2016)
Haptoglobin is a major acute phase protein in bovines and reportedly increases in serum and milk whey during mastitis, highlighting its potential as a diagnostic biomarker. Since haptoglobin is known to undergo tissue specific glycosylation resulting in different isoforms, this study was undertaken to characterize the isoforms of haptoglobin. Milk whey fraction and serum obtained from animals with or without clinical mastitis in Puducherry, India, were subjected to SDS-PAGE followed by western blot and immuno-detection of haptoglobin protein. All subunits (β, α1 and α2) of haptoglobin protein were detected in serum sample obtained from clinical cases. However, only the β-subunit was detected in milk whey fraction obtained from the respective animals. Similar results were observed with milk whey fractions from subclinical cases indicating difference in isoform of haptoglobin detected in milk whey from serum. This was further supported by RT-PCR (Reverse Transcription Polymerase Chain Reaction) analysis of haptoglobin gene (Hp) confirming the tissue specific origin of haptoglobin.